Dispersion of refractive index of thin films CdI2 and ZnI2 - Kovalenko, E. N.; Miloslavsky, V. K.; Yunakova, O. N. (НТК “Інститут монокристалів” Національної академії наук України, 2010)
A dispersion of refractive index in thin films CdI2 and ZnI2 are measured in the interval of lengths waves 300-1000 nanometers, its processing with the help monooscillator model is in the good agreement with data of experiment. The optical inductivity  of two compounds is determined by retrieved parameters of this model, this optical inductivity are utilised for the further analysis of excitons states in CdI2 and ZnI2, and, in particular, for determination of 1s excitons radius. The retrieved values аех are close to parameters of a unit cell of two compounds, that indicates a fitting of excitons in two compounds to excitons of intermediate electron - hole connection
Keywords: thin films; refractive index; absorption spectra